Alexander Pasqualini (1493-1559) architect en vestingbouwkundige (Bulletin KNOB, 1991)
The Italian Alexander Pasqualini, as artillery master in the service of the Lords of Egmond from about 1531 and as an architect in the service of the Duke of Gulik, Kleef and Berg, introduced early Renaissance architecture in the Low Countries. Pasqualini, born at Bologna on the 5th of May 1493 was trained an architect and fortress engineer at Rome in an environment dominated by famous Renaissance architects.After the capture and plundering of Rome in 1527 by the army of Charles V many Italian artists and architects settled in European courts. Developments in offensive weapons required application of the youngest ideas on the field of fortresses as these were carried out in 15th century Italy.Alexander Pasqualini probably came to the north on the request of young Maximiliaan van Egmond, son of Floris van Egmond, one of Emperor Charles V’s most important commanders-in-chief. His tower of the Church of St. Nicholas at IJsselstein (1535) is the first monumental building of an Italian Renaissance architect in northern Europe.In addition to the tower of IJsselstein the Castle of Buren, which had been restored, enlarged and embellished by Earl Floris van Egmond since the twenties of the 16th century, is one of Pasqualini's other important buildings in the Low Countries. Under the guidance of Pasqualini the castle was rebuilt as a palace in Italian style with a gallery with characteristic columns, arches and with medaillions in the pendentives. With Thomas Vincedor's gallery of the Castle of Breda this gallery meets one of the criteria of Italian Renaissance palaces: the open gallery enclosing a square courtyard.For Information about Pasqualini's fortifications we are driven back on written sources entirely. He provided several towns on the territory of Maximiliaan van Egmond with new fortifications in the context of the war with the Duchy of Guelre-Zutphen. Pasqualini advised other towns at the improvement of their fortifications as well. After the sudden death of Maximiliaan van Egmond he entered the services of his previous employer's enemy, Willem V, Duke of Gulik, Kleef and Berg.The construction of castle and citadel at Jülich certainly is Pasqualini's most important project in the service of Willem V. As typical of a Renaissance fortification castle and citadel form an inseperable unity. The chapel is the first church in Renaissance style in Germany.Pasqualini was active in all of the Duke's territory. After his death his sons Maximiliaan and Johan would finish the projects as started by their father. In 1568 the working territory was divided in two. Maximiliaan remained architect of Gulik and Berg and his younger brother Johan was appointed to architect for Kleef and Mark till the death of his brother in 1572, when the supervision on the building activities was united in one person again.Johan Pasqualini the Younger was appointed to ducal architect in 1586. He was commissioned only one new project, the extension and fortification of Mülheim, a small town near Cologne. With the death of Alexander Pasqualini the Younger (1620), who was regularly involved in the fortification of Düsseldorf between 1608 and 1620 the tradition of the architects Pasqualini came to an end.The next generations lived as landed nobility in the German-Dutch borderland and strove for expansion of the family's landed property. With the death of Anna Judith Elisabeth Pasqualini in 1761 the family became extinct and by Anna's marriage with Baron Johan Herman van Hövell in 1737 all of the family's properties passed over to the family Van Hövell.In August 1543 Earl Maximiliaan van Egmond came to Kampen to confer with the Provincial Diet on acts of war and a financial contribution to the imperial offensive against Duke Willem V in the Guelders War, which raged in all violence in 1542 and 1543. Maximiliaan brought his fortress engineer to Kampen to explore possibilities on improvement of the fortifications.The municipality of Kampen was not interested in the plan before 1554 in the context of the planned improvement of the harbour at the Gate of Hagen and the renewal of the quay-walls at the IJssel-tower. The cipher flanked by the date 1543 is an additional datum to the attribution of the map to Alexander Pasqualini. This cipher shows a strong resemblance with the initials of Alexander Pasqualini the Younger as preserved on two maps (1592 and 1605) in the municipal archives of Wesel (G.). This cipher can also be found on a plan of the Castle of Grave, made by Pasqualini in 1541 and being kept in the Belgium general state archives at Brussel (a 19th century copy in the state archives in Noord-Brabant at 's-Hertogenbosch).His map of Kampen (1543) is being kept in the municipal archives of Kampen. The fortifications to the northwest side of Kampen are rendered to mark the situation of the artillery-wall proposed by Pasqualini, but never realized. These fortifications have been represented in detail. The scale corresponds with later plans of the location as well.The plan of the castle at Grave made by Pasqualini can be compared with the map of Kampen in the way of accuracy. This map shows the results of the building campaign which took place between 1515 and 1541 and renders the direct environment of the castle and the situation of the complex with respect to the city rampart of Grave as well. With the map of Kampen this plan gives an excellent impression of Pasqualini's detailed working method.